2011
DOI: 10.1111/j.1530-0277.2011.01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin‐Releasing Factor Acting on Corticotropin‐Releasing Factor Receptor Type 1 is Critical for Binge Alcohol Drinking in Mice

Abstract: Background The corticotropin releasing factor (CRF) system has been implicated in the regulation of alcohol consumption. However, previous mouse knockout (KO) studies using continuous ethanol access have failed to conclusively confirm this. Recent studies have shown that CRF receptor 1 (CRFR1) antagonists attenuate alcohol intake in the limited access “drinking in the dark” (DID) model of binge drinking. To avoid the potential non-specific effects of antagonists, in the present study we tested alcohol drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 63 publications
(93 reference statements)
4
54
1
Order By: Relevance
“…In the case of EtOH drinking, studies using CRF 1 manipulations have found that these receptors are involved in EtOH effects, especially when tested in postdependent animals, in lines of rodents bred for elevated EtOH consumption or under the effects of stress (Heilig and Koob, 2007;Pastor et al, 2011). Recent data also suggest that CRF 1 can play a role in EtOH drinking even in nondependent or nonstressed animals if they are tested under conditions that facilitate elevated or binge-like drinking (Lowery and Thiele, 2010;Pastor et al, 2011;Kaur et al, 2012). Thus, as proposed previously (Breese et al, 2004;Heilig and Koob, 2007;Lowery and Thiele, 2010;Kaur et al, 2012), CRF 1 manipulations might be excellent candidates for the development of pharmaceutical interventions for excessive EtOH drinking or EtOH abuse in dependent, genetically susceptible, or stress-prone individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of EtOH drinking, studies using CRF 1 manipulations have found that these receptors are involved in EtOH effects, especially when tested in postdependent animals, in lines of rodents bred for elevated EtOH consumption or under the effects of stress (Heilig and Koob, 2007;Pastor et al, 2011). Recent data also suggest that CRF 1 can play a role in EtOH drinking even in nondependent or nonstressed animals if they are tested under conditions that facilitate elevated or binge-like drinking (Lowery and Thiele, 2010;Pastor et al, 2011;Kaur et al, 2012). Thus, as proposed previously (Breese et al, 2004;Heilig and Koob, 2007;Lowery and Thiele, 2010;Kaur et al, 2012), CRF 1 manipulations might be excellent candidates for the development of pharmaceutical interventions for excessive EtOH drinking or EtOH abuse in dependent, genetically susceptible, or stress-prone individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Current research shows that other neuroadaptive changes associated with alcoholism are also related to CRF and CRF 1 . CRF 1 antagonists can block excessive alcohol drinking and the increases in anxiety-like symptoms after a history of EtOH dependence (Breese et al, 2004;Heilig and Koob, 2007;Lowery and Thiele, 2010;Kaur et al, 2012). In addition, they can prevent stress-induced reinstatement of EtOH-seeking in postdependent rodents (Heilig and Koob, 2007;Lowery and Thiele, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both CRF and CRF 1 knockout mice show reduced ethanol intake and blood ethanol concentrations in a murine model of scheduled, limited access to ethanol (“drinking-in-the-dark”) that can produce binge-like intake (Kaur et al, 2012), suggesting an early role for CRF in neuroadaptations associated with the binge/intoxication stage of the addiction cycle. Perhaps accordingly, systemic administration of small-molecule CRF 1 antagonists can reduce binge-like but not non-binge-like ethanol intake in C57BL/6J mice and outbred rats (Lowery et al, 2010;Cippitelli et al, 2012;Simms et al, 2013) (but see (Giardino and Ryabinin, 2013) for additional findings suggesting that these effects may not be specific for ethanol).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, both global (Chu et al, 2007) and conditional brain-specific Crhr1 knockout (Crhr1[NestinCre]) mice (Molander et al, 2012) show reduced ethanol intake during withdrawal in the postdependent state compared with their wildtype littermates. CRF 1 -receptor knockout mice also drink less 20% v/v ethanol under basal conditions (Pastor et al, 2011), and both CRF and CRF 1 knockout mice show reduced ethanol intake and blood ethanol concentrations in the bingelike drinking-in-the-dark paradigm of limited ethanol access (Kaur, Li, Stenzel-Poore, & Ryabinin, 2012), suggesting an early role in neuroadaptations associated with the binge/intoxication stage. Consistent with this hypothesis, systemic administration of small-molecule CRF 1 antagonists can reduce binge-like, but not nonbinge-like, ethanol intake in C57BL/6 J mice and outbred rats (Cippitelli et al, 2012;Lowery et al, 2010;Simms, Nielsen, Li, & Bartlett, 2013; but see Giardino & Ryabinin, 2013, for a suggestion that these effects may not be specific for ethanol).…”
Section: Between-system Neuroadaptations That Contribute To Compulsivmentioning
confidence: 98%